2007
DOI: 10.1523/jneurosci.3005-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Source of Afterdischarge Activity in Neocortical Tonic–Clonic Epilepsy

Abstract: Tonic-clonic seizures represent a common pattern of epileptic discharges, yet the relationship between the various phases of the seizure remains obscure. Here we contrast propagation of the ictal wavefront with the propagation of individual discharges in the clonic phase of the event. In an in vitro model of tonic-clonic epilepsy, the afterdischarges (clonic phase) propagate with relative uniform speed and are independent of the speed of the ictal wavefront (tonic phase). For slowly propagating ictal wavefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 40 publications
14
31
0
Order By: Relevance
“…We monitored seizure activity by performing current-clamp recordings from hippocampal CA3 pyramidal neurons using the gramicidinperforated patch method. In accordance with previous work, we could distinguish two phases of the seizure episodes: (1) the initial ictal-like phase (also referred to as the "tonic" phase) and (2) the after-discharge phase (also referred to as the "clonic" phase) (Higashima et al, 1996;Trevelyan et al, 2007;Isomura et al, 2008). The ictal phase was characterized by a Ͼ40 mV membrane potential depolarization upon which occurred high-frequency, low-amplitude discharges (Fig.…”
Section: Endogenous Adenosine Release Modulates Seizure Duration and supporting
confidence: 88%
“…We monitored seizure activity by performing current-clamp recordings from hippocampal CA3 pyramidal neurons using the gramicidinperforated patch method. In accordance with previous work, we could distinguish two phases of the seizure episodes: (1) the initial ictal-like phase (also referred to as the "tonic" phase) and (2) the after-discharge phase (also referred to as the "clonic" phase) (Higashima et al, 1996;Trevelyan et al, 2007;Isomura et al, 2008). The ictal phase was characterized by a Ͼ40 mV membrane potential depolarization upon which occurred high-frequency, low-amplitude discharges (Fig.…”
Section: Endogenous Adenosine Release Modulates Seizure Duration and supporting
confidence: 88%
“…It was found that the bursts within a seizure became bidirectional, with different propagation patterns at different frequencies (Derchansky et al, 2006). Recent work has also shown that the direction of propagation for discharges during a seizure are variable, and it was found that there is no single source of discharge activity; rather, the source is continuously changing (Trevelyan et al, 2007;Merlin, 2009). In this study we further demonstrate the above findings by estimating the directionality index with the PCMI.…”
Section: Application To Real Neuronal Populationsupporting
confidence: 70%
“…Patient C2 was in partial status epilepticus throughout the recording period and did not show the same sudden recruitment pattern, instead showing surges of activity, which likewise, spread slowly across the MEA (five seizures; mean 0.18, range 0.12–0.26 mm s −1 ). These recordings show that seizures in vivo propagate with remarkable similarity to the slow ictal wavefronts in the in vitro 0 Mg 2+ model101226 (albeit, far slower than epileptiform clonic discharges recorded in this model27 or epileptiform events recorded in disinhibited slices282930, both of which propagate between 10 and 200 mm s −1 , but notably, both also represent instances where there is little or no effective feedforward inhibition to slow propagation). There are further clear parallels between in vivo and in vitro activity with regard to the spatially sharp drop in firing activity at the wavefront (Figs 2g and 4f) and the widely and rapidly distributed 2–50 Hz signal (Fig.…”
Section: Resultsmentioning
confidence: 65%